Surface Rutilization of Anatase TiO 2 Nanorods for Creation of Synergistically Bridging and Fencing Electron Highways - Chen, Jiazang (2017)
In a photoelectrochemical cell, the most concerned issue in the nanostructured TiO2 electrode is the charge transport, which consists of the internal movement of electrons in TiO2 nanostructures and the intergrain charge transfer. Here, inspired by electrochemical studies on different polymorphs of TiO2, it is proposed to bridge the adjacent building blocks and fence the electron transport highways in TiO2 electrodes by surface rutilization of anatase nanorods. The ultrathin rutilized layer completely coated on the anatase surface has a slightly higher conduction band edge than that of anatase. The obtained surface rutilized anatase nanorods can not only improve the intergrain charge transfer while maintaining fast electron transport within anatase but also minimize the internal energy consumption and protect the electrons in TiO2 electrodes from recombination, which are beneficial to the charge collection and can significantly improve the photovoltaic performance of photoelectrochemical cells.